A pathogenic tau fragment compromises microtubules, disrupts insulin signaling and induces the unfolded protein response - Tong Guo (Acta Neuropathologica Communications, 2019)
Abstract Human tauopathies including Alzheimer’s disease, progressive supranuclear palsy and related disorders, are characterized by deposition of pathological forms of tau, synaptic dysfunction and neuronal loss. We have previously identified a pathogenic C-terminal tau fragment (Tau35) that is associated with human tauopathy. However, it is not known how tau fragmentation affects critical molecular processes in cells and contributes to impaired physiological function. Chinese hamster ovary (CHO) cells and new CHO cell lines stably expressing Tau35 or full-length human tau were used to compare the effects of disease-associated tau cleavage on tau function and signaling pathways. Western blots, microtubule-binding assays and immunofluorescence labeling were used to examine the effects of Tau35 on tau function and on signaling pathways in CHO cells. We show that Tau35 undergoes aberrant phosphorylation when expressed in cells. Although Tau35 contain the entire microtubule-binding region, the lack of the amino terminal half of tau results in a marked reduction in microtubule binding and defective microtubule organization in cells. Notably, Tau35 attenuates insulin-mediated activation of Akt and a selective inhibitory phosphorylation of glycogen synthase kinase-3. Moreover, Tau35 activates ribosomal protein S6 kinase beta-1 signaling and the unfolded protein response, leading to insulin resistance in cells. Tau35 has deleterious effects on signaling pathways that mediate pathological changes and insulin resistance, suggesting a mechanism through which N-terminal cleavage of tau leads to the development and progression of tau pathology in human tauopathy. Our findings highlight the importance of the N-terminal region of tau for its normal physiological function. Furthermore, we show that pathogenic tau cleavage induces tau phosphorylation, resulting in impaired microtubule binding, disruption of insulin signaling and activation of the unfolded protein response. Since insulin resistance is a feature of several tauopathies, this work suggests new potential targets for therapeutic intervention.